Meningkatkan Hasil Belajar Siswa Dengan Menerapkan Model Case Method Pada Pembelajaran Tematik Di Kelas IV UPT SD Negeri 060870 Medan Timur - Rahmawati, Neny (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this study was to improve student learning outcomes by using the case method learning model in thematic lessons in class IV UPT SD Negeri 060870 Medan Timur. This research was conducted in class IV UPT SD Negeri 060870 Medan Timur which is located at Jalan Gunung Krakatau No.196, Pulo Brayan Darat I, Medan Timur District, Medan City, North Sumatra, 20236. The implementation of this research was in semester I, this research was Class Action (PTK). The research steps involved are planning, acting, observing, reflecting, and evaluating and consist of 2 cycles. The subjects in this study were fourth grade students of UPT SD Negeri 060870 Medan Timur for the Academic Year 2022/2023 with a total of 26 students consisting of 11 boys and 15 girls. The object of this study is the learning outcomes in thematic lessons using the case method learning model in class IV UPT SD Negeri 060870 Medan Timur. From the results of this classroom action research several conclusions were obtained, namely: The use of the case method learning model was able to improve the learning outcomes of class IV UPT SD Negeri 060870 Medan Timur in thematic lessons. The average student learning outcomes increased from 50% to 69% in cycle I to 77% in cycle II. Student activities and student learning outcomes in learning increase and complete.